Detection of Plasmon Coupling between Silver Nanowires Based on Hyperspectral Darkfield and SERS Imaging and Supported by DDA Theoretical Calculations1. Issue 4 (6th January 2016) - Santos, Jonnatan J.; Ivanov, Evandro; dos Santos, Diego P.; Toma, Henrique E.; Corio, Paola
Abstract: We report the unprecedented observation of plasmon coupling between silver nanowires, showing how the surface‐enhanced Raman scattering depends upon this interaction and how the spectrum can be shaped by the hot spot. Such observations were accomplished by Raman spectroscopy mapping of silver nanowires modified with rhodamine. The local spectra on the hot spots were measured by darkfield hyperspectral microscopy, a powerful but uncommonly used technique that is capable of determining the location, structure, and spectra of the hot spots. The result obtained by the simulation of two parallel nanowires based on the discrete dipole approximation (DDA) method was in excellent agreement with the results obtained experimentally. Abstract : Coupling between silver nanowires : The observation of plasmon coupling between silver nanowires is reported. The authors demonstrate that the surface‐enhanced Raman scattering depends on this interaction—and that the spectrum can be shaped by the hot spot.